2002
DOI: 10.1590/s1516-31802002000300003
|View full text |Cite
|
Sign up to set email alerts
|

Risk-of-Malignancy Index in preoperative evaluation of clinically restricted ovarian cancer

Abstract: The risk-of-malignancy index using ultrasound morphological score, serum CA 125 levels and menopausal status might be of value in the preoperative assessment of ovarian carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 19 publications
2
38
0
5
Order By: Relevance
“…5 In a cross sectional study on 158 patients, it was shown that RMI at a cut off 200 had sensitivity 73% and specificity 86%. 6 Study by Ulsoy and co workers on 296 women concluded RMI identified malignant cases more accurately than any other individual criterion in diagnosing ovarian cancer. 7 Terzic M and co-workers in their study on 81 patients Sensitivity of RMI was 83.33%, specificity was 94.12%, positive predictive value was 89.29% and negative predictive value was 90.57% with cut off value of at 200.…”
Section: Discussionmentioning
confidence: 99%
“…5 In a cross sectional study on 158 patients, it was shown that RMI at a cut off 200 had sensitivity 73% and specificity 86%. 6 Study by Ulsoy and co workers on 296 women concluded RMI identified malignant cases more accurately than any other individual criterion in diagnosing ovarian cancer. 7 Terzic M and co-workers in their study on 81 patients Sensitivity of RMI was 83.33%, specificity was 94.12%, positive predictive value was 89.29% and negative predictive value was 90.57% with cut off value of at 200.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have suggested a cut-off value for RMI 1-3 of 200 [9][10][11]16,18]. Using tumor size, Yamamoto et al [12] developed their own RMI, Jung-Woo Park, et al Four RMIs in pelvic masses and named it RMI 4 (using a cutoff level of 450).…”
Section: Discussionmentioning
confidence: 99%
“…Yamamoto et al [12], who created their own model of a malignancy risk index, added the parameter of tumor size (S) to the RMI, and have termed it RMI 4. Retrospective and prospective validation of the four versions of the RMI have been conducted in different clinical studies [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], where a cutoff value of 200 for RMI 1-3 and 450 for RMI 4 showed the best discrimination between benign and malignant pelvic masses, with high levels of sensitivity and specificity (sensitivity 51%-90%, specificity 51%-97%). The main advantage of four RMIs is that it is a simple scoring system that can be applied directly into clinical practice without the introduction of expensive or complicated methods (such as computed tomography scan, magnetic resonance imaging, and wholebody positron emission tomography).…”
Section: Jung-woo Park Et Al Four Rmis In Pelvic Massesmentioning
confidence: 99%
“…Another reason to propose this two step approach is the high levels of CA125 in some benign ovarian masses such as endometrioma and tuberculosis, which might mislead the practitioner to malignancy if CA125 is used in the first step (Campos et al, 2002;Moolthiya, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Tumors of the ovary generally present as adnexal masses (Campos et al, 2002). Proper management of an adnexal mass depends greatly on predicting the chance of malignancy to decide correctly by whom and where the patient should be operated on (Marjunath, 2001;Mederiros, 2005).…”
Section: Introductionmentioning
confidence: 99%